Atomistic insights into the morphological dynamics of gold and platinum nanoparticles: MD simulations in vacuum and aqueous media - Evangelos Voyiatzis; Eugenia Valsami-Jones; Antreas Afantitis (Beilstein Journal of Nanotechnology, 2024)
The thermal response of gold and platinum spherical nanoparticles (NPs) upon cooling is studied through atomistic molecular dynamics simulations. The goal is to identify the morphological transformations occurring in the nanomaterials as well as to quantify their dependence on temperature, chemistry, and NP size. For diameters smaller than 3 nm, the transition temperature from a melted/amorphous to a highly crystalline state varies considerably with NP size. For larger NPs, the transition temperature is almost diameter-independent, yet it differs considerably from the transition temperature of the respective bulk materials. The platinum NPs possess a higher level of crystallinity than the gold counterparts under the same conditions because of the stronger cohesive forces that drive the crystallization process. This observation is also supported by the simulated X-ray powder diffraction patterns of the nanomaterials. The larger NPs have a multifaceted crystal surface, and their shape remains almost constant regardless of temperature variations. The smaller NPs have a smoother and more spherical surface, and their shape varies greatly with temperature. By studying the variation of nano-descriptors commonly employed in QSAR models, a qualitative picture of the NPs’ toxicity and reactivity emerges: Small/hot NPs are likely more toxic than their large/cold counterparts. Because of the small size of the NPs considered, the observed structural modifications are challenging to be studied by experimental techniques. The present approach can be readily employed to study other metallic and metal oxide nanomaterials.